Three Generations of Distance Education Pedagogy - Anderson, Terry (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
In this presentation Terry defines three pedagogical models that have defined distance education programming - behavioural/cognitive, constructivist, and connectivist. He talks about the challenges and opportunity afforded by each model, with a focus on the emergent development of connectivism.